2013
DOI: 10.3109/0886022x.2013.808956
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caveolin-1 and P-ERK1/2 on Ang II-induced glomerular mesangial cell proliferation

Abstract: This study explored the effects of caveolin-1, p-ERK1/2 and transient receptor potential channel 6 (TRPC6) on angiotensin II (Ang II)-induced glomerular mesangial cell (GMC) proliferation, and investigated the role of Ang II on GMC proliferation. GMC cultures were divided into Control, Ang II (Ang II 10 À7 mol/L), PD98059 (Ang II 10 À7 mol/L þ PD98059 5 Â 10 À5 mol/L) and MbCD groups (Ang II 10 À7 mol/L þ MbCD 10 À2 mol/L). GMCs proliferation was measured by the methyl thiazolil tetracolium and trypan blue ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
(27 reference statements)
3
6
0
Order By: Relevance
“…Expression of TRPC6 protein in human MCs was also reported by several other groups (87,110,119,131,158,233 Diabetic nephropathy is a major and devastating complication of diabetes. At the very onset of diabetes, a dominant pathophysiological characteristic is the development of renal glomerular hyperfiltration (13,214).…”
Section: Expression Of Trpc6 In Glomerular Mcssupporting
confidence: 70%
See 3 more Smart Citations
“…Expression of TRPC6 protein in human MCs was also reported by several other groups (87,110,119,131,158,233 Diabetic nephropathy is a major and devastating complication of diabetes. At the very onset of diabetes, a dominant pathophysiological characteristic is the development of renal glomerular hyperfiltration (13,214).…”
Section: Expression Of Trpc6 In Glomerular Mcssupporting
confidence: 70%
“…This high-glucose/diabetes-induced decrease in TRPC6 protein expression was MC specific because this response was not observed in the aorta and the heart tissue isolated from those diabetic rats (72) and in high-glucose-treated podocytes (71). Since our study was conducted in rats only 2 weeks after STZ injection, the decrease in abundance of TRPC6 (158,233). In addition, TRPC6 also contributed to phenylephrine (a1-adrenergic receptor agonist)-induced MC proliferation (110).…”
Section: Expression Of Trpc6 In Glomerular Mcsmentioning
confidence: 94%
See 2 more Smart Citations
“…Another study by Zhuang et al also demonstrated that the inhibition of ERK1/2 signaling via U0126 could markedly block uric acid induced rat mesangial cell proliferation [28]. Similar results were also found in an Ang II-induced glomerular mesangial cell (GMC) proliferation study, and the results revealed that p-ERK1/2 acted as an upstream signaling molecule for TRPC6 [29]. Another study showed that FK506 could activate the ERK1/2 signaling cascade in rat renal mesangial cells [30].…”
Section: Introductionsupporting
confidence: 68%